Book recommendation system for utilisation of library services. (27th December 2010) - Kuroiwa, Takanori; Bhalla, Subhash
In addition to using the many conventional approaches for making recommendation systems, this paper proposes a complementary recommendation methodology. It is focused on book recommendation. It proposes to make a comprehensive data repository of existing books, available at the level of the user (in a library or a personal bookshelf). Further, by retrieving web reviews of available books and new books by using existing web services, an infrastructure has been developed for need-based book recommendation system. Implementation results show that our book recommendation allows a user to eliminate irrelevant books and presents the desired books to the user from given book set. The proposed book recommender is one of the first systems in terms of focusing on meeting individuals' needs rather than calculating similarity or preferences automatically, which is adopted by the traditional recommender system.